Desertification risk assessment in Turkey based on environmentally sensitive areas. (July 2020) - Uzuner, Çağlar; Dengiz, Orhan
Highlights: Demonstration of a flexibility of ESAs approach for complex and specific environments. Refinement of desertification susceptibility indices in MEDALUS by geostatistics. Generating a national desertification map of Turkey by assessing ESAs. Abstract: Turkey's many and varied landscapes face the challenge of degradation and ultimately desertification due to soil problems that include organic matter deficiency, salinity-alkalinity, compaction and erosion and the loss of biological productivity. Yet, without fully accepted indicators for the monitoring and reporting of degradation, desertification cannot be definitively confirmed at the regional or national level. Environmentally Sensitive Areas Index (ESAI) was developed to identify areas vulnerable to the threat of desertification in the "MEDALUS" (Mediterranean Desertification and Land Use) model, which was chosen as the basis for the present study. Variables and thematic indicators such as climate, soil quality, land use, amount of plant cover and management are included in the ESAI. However, studies made at international scale are not sufficiently sensitive regarding data quality for calculations and modelling at the national scale. Therefore, aim of the present study was to i) create a modelling approach that can respond to national needs for monitoring and reporting on soil and land degradation by modifying the MEDALUS method, and ii) generate a national desertification map of Turkey by assessing environmentally sensitive areas (ESAs) at the national scale using this model. Results classified more than 60% (51.5 mil. ha) of the total area as fragile and critical, while only about 12% of the Turkey' land was indicated as area non-affected by the desertification risk. In the determination of ESAI, the parametric and spatial models were re-designed according to data and impact value by using GIS software-supported geographical analysis. With that added-on facility, MEDALUS can be automatically re-run with updated data or the change-of-influence line, and thus the change of land quality can also be monitored.